UPAYA PENINGKATAN GERAK DASAR MELALUI PERMAINAN ROK GEBUG PADA SISWA KELAS V SD NEGERI DUKUHJATI KIDUL 02 KABUPATEN TEGAL TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2013)
Issues raised in this study is How to Increase the Basic Motion Game through Rok Gebug In Class V studentsof SD Negeri Tegal Dukuhjati Kidul District 02 in 2013.Object of this study is the fifth grade students of SDNegeri 02 Dukuhjati Kidul Regency Tegal number of 32 students. To obtain the appropriate data in this studyusing PTK (Classroom Action Research). For TOD consists of four stages: planning, action, observation andreflection. The research instrument using the check list to record the attitudes and events that occur in learningdeemed important and has been set to be investigated. From the observations obtained with the help of a checklist can be obtained that the percentage of cognitive abilities, affective and psychomotor of fifth grade elementaryschool students Dukuhjati Kidul Regency Tegal 02 shows that in the first cycle of cognitive learning outcomesof students reached 68.75%, student learning outcomes the affective aspect reached 70.62% and psychomotoraspects of learning outcomes reached 56.25%. After the improvement of the learning activity in the second cyclethen an increase in student learning outcomes for all aspects, ie to be 84.68% cognitive, affective aspects to be79.06% and a 82.61% psychomotor aspects. Some researchers suggest among other things, learning basicmovements with skirt gebug game approach can be an alternative to be applied. Because it can provide directlearning experiences to students through the play and the development of scientific skills and a good attitude forstudents. Also can be used as an alternative to overcome the lack of infrastructure support at school so it can be applied as a learning variations.